2013
DOI: 10.1002/jbm.b.33019
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial property expressed by a novel calcium phosphate glass

Abstract: We have developed a calcium phosphate glass (CPG) doped with Zn2+ or F− or combined Zn2+ and F− ions, which are naturally found in the human body and play a dual role in bone formation and antibacterial activity. Previously, we have demonstrated that this family of CPGs has superior osteoconductive and resorbable properties in vivo. This study aimed to investigate the antibacterial property of CPGs incorporating Zn2+ and/or F−. We used Streptococcus mutans as a model organism because it is one of the major hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 62 publications
0
19
0
1
Order By: Relevance
“…This might be responsible for lower amounts of released Zn or other elements favoring biocompatibility, as confirmed in the present study. Finally, Zn-doped glass-ceramic materials have shown antibacterial properties [13]; an important factor for use in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be responsible for lower amounts of released Zn or other elements favoring biocompatibility, as confirmed in the present study. Finally, Zn-doped glass-ceramic materials have shown antibacterial properties [13]; an important factor for use in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Tailoring ionic dissolution (= biointeractivity) from bioceramic materials is key to achieving specific biological responses, since many elements released by these materials, such as Si 4+ , P, Zn 2+ , Mg 2+ , or Ca 2+ ions, participate in signaling pathways and intracellular interactions in the human body [10]. In particular, Mg has been shown to influence biomineralization and apatite crystal formation in bone and teeth [11], while Zn has been reported to affect bioactivity, biocompatibility and antimicrobial properties when incorporated into the structure of various glasses [12,13]. However, use of bioceramic materials alone has been limited by poor mechanical strength [8].…”
Section: Introductionmentioning
confidence: 98%
“…For example, dissolution studies using 0.05 g glass particulates immersed in a 25 ml potassium acetate solution (pH = 6) at 37°C for 4 h revealed that the amount of Ca 2+ released from the F-CaP glass (10.9 ± 0.40 ppm) was less than half of that (24.3 ± 0.64 ppm) from the CaP glass. 42 …”
Section: Discussionmentioning
confidence: 99%
“…These findings may be attributed to zinc’s uptake into bacterial cells, where it acts as an inhibitor of ATP synthesis, whereas fluoride is known to disrupt bacterial enzymes and membrane function. 42 In addition, the antimicrobial effects of zinc and fluoride have been shown not only effective for planktonic cells, but also for single-species biofilms. 43 On the other hand, studies have shown that when incorporated in conjunction with calcium phosphate materials, zinc expedites bone formation by decreasing osteoclast activity while increasing the rate of osteoblast adhesion and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…В ряде исследований синтези-рованные золь-гель методом пленки, содержащие ионы серебра [7,8], цинка и фтора [9], меди и серебра [10], оксидов теллурия и ванадия [11], внедренные в структуру стекла или керамиче-ского покрытия, показывали выраженные анти-микробные свойства, снижая численности таких микроорганизмов, как E. coli, Enterococcus faecalis, Streptococcus mutans, Listeria monocytogenes, Pseudomonas aeruginosa, Salmonella enterica.…”
Section: Introductionunclassified